Analysis of capacitive currents in the winding of a high voltage measuring autotransformer - Бржезицький, Володимир Олександрович; Гаран, Ярослав Олександрович (Technology audit and production reserves, 2016)
The paper analyzed the distribution of capacitive currents in the winding of measuring high-voltage autotransformer at its operating frequency 50 (60) Hz. It is revealed that idling high-voltage autotransformer at significant nominal dividing coefficient these currents can acquire essential values against the current idling, which can affect the accuracy of large-scale conversion of high-voltage measuring autotransformers. The paper presents an approach to account values of interlayer capacitive currents in the windings of high-voltage autotransformers to clarify the distribution of voltage on their low-voltage (output) winding parts. It is shown that the distribution of capacitive currents significantly different to the first, last and middle layers of windings that must be considered when designing the windings of high-voltage autotransformers and calculate the number of turns in the respective high-voltage and low-voltage parts of windings. This analysis is particularly important for the development of standard measurement tools using high-voltage autotransformer scale transformation.